E-Prescription in Nigeria: A Survey - Adebayo Omotosho; Justice Emuoyibofarhe; Peace Ayegba; Christoph Meinel (Journal of Global Pharma Technology, 2019)
Electronic prescribing or Electronic prescription (EP) is the computer-based electronic generation and transmission of a prescription.  EP systems help to increase accuracy and safety of patient prescription and reduce costs through improved legibility and electronic delivery. The motivation for EP is greater safety of drug use and to counter the current unacceptable levels of adverse drug events. This study evaluated the feasibility of hospitals in Nigeria to adopt an EP system. A survey was conducted in four hospitals in Nigeria to determine the economic, technical and organisational feasibility of adopting e-prescribing. Respondents included 42 medical practitioners - doctors, pharmacists, pharmacy technicians and assistants - working at the hospitals at the time of the survey. Respondents felt that implementation of an EP system is economically feasible (p=0.031) and organisationally feasible (p=0.032) but were ambivalent as to whether it is technically feasible (p=0.446). However, inadequate funding by the government does not provide for the health sector to acquire the necessary resources and training skills.